PENGARUH KINERJA KEUANGAN DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Rachmansyah, Alfian Muhammad; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out and to prove empirically the influence of profitability, liquidity, and investment decision to the influence of profitability, liquidity, and investment decision to the firm value which has been done by using Price to Book Value (PBV).The research sample has been carried out by using purposive sampling technique with the predetermined criteria, i.e.: first, food and beverages companies which are listed in Indonesia Stock Exchange in 2013-2016 periods; second,food and beverages companies which are listed in the IDX and have ever published their financial statement which has been continuously audited and presented in rupiah currency. The population is 15 food and beverages companies, 8 food and beverages companies have been obtained as samples in 2013-2016 observation periods. The analysis technique has been carried out by using classic assumption test and hypothesis test also multiple regressions analysis with the application of SPSS (Statistical Product and Service Solutions).Based on the result of multiple regressions analysis with its significance level is 5%, therefore the result of the research shows that profitability gives significant and positive influence to the firm value, liquidity does not give any influence to the firm value, and investment decision gives significant and positive influence to the firm value. Simultaneously all independent variables in this research give significant influence to the firm value. Furthermore, the result of regressions estimation shows that the prediction capability of 3 independent variables to the firm value is 81 % whereasthe remaining is 19% is influenced by other factors which are not included in the model of this research.Keywords: Profitability, liquidity, investment decision, firm value.